Defining Values for Controlled Attenuation Parameter and Liver Stiffness in Youth Without Liver Disease - Garcia-Hermoso, A (Springer Nature, 2022)
Background: We aimed to determine the reference values to define an age-specific normal range of controlled attenuation parameter (CAP, a measure of liver steatosis) and liver stiffness measurement (LSM) values assessed by ultrasound-based transient elastography in adolescents without underlying liver disease. Methods: A total of 462 participants were included in this cross-sectional study using data from NHANES 2017–2018. LSM and CAP were carried out using the FibroScan® M-probe. Anthropometric, metabolic and hematological parameters were measured. Results: The median CAP was 199.0 dB/m (150.0–245.0 dB/m, 10th to 90th percentiles) and the median LSM was 4.7 kPa (3.4–6.3 kPa, 10th to 90th percentiles) for ages 12–19.9 years. Regression analyses show that the CAP and LSM were not positively correlated with age (boys CAP R2 = 0.001, p = 0.576 and LSM R2 = 0.012, p = 0.096; girls CAP R2 = 0.011, p = 0.113 and LSM R2 = 0.006, p = 0.236). Finally, CAP was positively associated with LSM in girls (β = 0.189, p = 0.005) but not in boys (β = −0.083, p = 0.202). Conclusions: The reference values indicated here for LSM and CAP will help in the screening of adolescents between ages 12 and 19.9 years and might serve as a useful method for identifying those youth at high risk of nonalcoholic fatty liver disease. Impact: The reference values indicated in this study for liver stiffness measurement (LSM) and controlled attenuation parameter (CAP) will help in the screening of adolescents between ages 12 and 19.9 years in clinical practice.The cutoffs of LSM and CAP might serve as a useful method for identifying those youth at high risk of nonalcoholic fatty liver disease. © 2021, The Author(s), under exclusive licence to the International Pediatric Research Foundation, Inc.